THE EFFECTIVENESS OF GIVING BIDARA LEAF EXTRACT AGAINST COLLAGEN DENSITY IN HEALING GINGIVAL INCISION WOUNDS IN WISTAR RATS - Mukti, Made Beratha; Jayawardhita, Anak Agung Gede; Arjana, Anak Agung Gde (Buletin Veteriner Udayana, 2022)
Bidara leaves (Ziziphus mauritiana lamk) are an alternative herbal in wound healing because they contain alkaloids, flavonoids, polyphenols, tannins, saponins and terpenoids. This study aims to determine how the effect of giving 100% bidara leaf extract on collagen density on the healing of gingival incision wounds in male wistar rats. This study used 24 male wistar rats. The sample consisted of three groups, namely the treatment group (P1), which was given 100% bidara leaf extract, the positive control group (K+) was given 10% povidone iodine, the negative control group (K-) was given 0.9% Nacl by smearing with cotton buds once a day. Mice were incised 15 mm in the gingival area to touch the alveolar bone vertically and applied with a cotton swab once a day. On the 8th day, all samples were biopsied on the gingiva of rats and made histological preparations to observe the amount of collagen density. Wound healing was observed with collagen growth. Observational data analyzed using the Kruskal-Wallis test showed that 100% bidara leaf extract had an effect on the healing process of the wistar rat gingival incision wound and followed by the Mann Whitney test showed that 100% bidara leaf extract was not significantly different from 10% povidone iodine but very significantly different from 0.9% NaCl solution. It can be concluded that giving 100% bidara leaf extract can accelerate the wound healing process seen from the density of collagen.